FACTORS OF FINANCIAL LITERACY, PERSONAL BEHAVIOR, AND FAMILY ON INVESTMENT AWARENESS OF GENERATION Z WORKERS - Dinar, Amanda (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2024)
This study aims to investigate the role of financial literacy, personal and family behaviors (such as saving behavior, self-control, spending patterns, and risk attitude) on investment awareness among Generation Z workers. Data were collected using purposive sampling through an online survey of Gen-Z workers who have worked or are currently working for at least 1 year and are aged 18-27 years in the Jabodetabek area. A total of 262 respondents were collected and then analyzed using PLS-SEM. Results show that financial literacy, self-control, saving behaviorrisk attitude, and family financial socialization have a significant influence on the investment awareness of Gen-Z workers. Meanwhile, self-control and spending patterns do not have a significant influence on the investment awareness of Gen-Z workers.